2016
DOI: 10.1590/0103-6440201600670
|View full text |Cite
|
Sign up to set email alerts
|

Edentulism, Severe Tooth Loss and Lack of Functional Dentition in Elders: A Study in Southern Brazil

Abstract: The aim of this study was to estimate self-reported prevalence of edentulism, severe tooth loss and lack of functional dentition in elders, and to identify potential associated factors. A population based cross-sectional study was carried out with 1,451 elders (≥60 years), in Pelotas, RS, Brazil. Crude and adjusted prevalence ratios were estimated using Poisson regressions. The prevalence of edentulism, severe tooth loss and lack of functional dentition was 39.3%, 60.9% and 82.7%, respectively. The factors pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
68
2
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 19 publications
15
68
2
16
Order By: Relevance
“…The prevalence rates of FDWHO and WDT among the Brazilian elderly were 10.82% and 8.45%, which were lower than those of the Japanese population (28.5%) in 2011 and low for the female population (26.2% against 31.6% among the Japanese elderly and 10.2% against 17% among the Brazilian elderly). These results are in agreement with those obtained for the southern Brazilian population in 2014 (17.3% for FDWHO), and in agreement with the SBbrasil 2010 (12.77% for FDWHO and 9.92% for WDT).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence rates of FDWHO and WDT among the Brazilian elderly were 10.82% and 8.45%, which were lower than those of the Japanese population (28.5%) in 2011 and low for the female population (26.2% against 31.6% among the Japanese elderly and 10.2% against 17% among the Brazilian elderly). These results are in agreement with those obtained for the southern Brazilian population in 2014 (17.3% for FDWHO), and in agreement with the SBbrasil 2010 (12.77% for FDWHO and 9.92% for WDT).…”
Section: Discussionsupporting
confidence: 91%
“…The earliest study identified in the current review was published in 1982 . Seven of the 24 studies included in this review were conducted in Brazil. The sample size considerably differed among the studies, and the number of participants ranged from 139 to 79 563.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size considerably differed among the studies, and the number of participants ranged from 139 to 79 563. The results that were analysed in the current review were mainly derived from cross‐sectional studies (n = 21) . The mean score attributed to the methodological quality was 15.7; the scores ranged from 14 to 18.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 The findings of foreign authors are controversial in this regard, as some do not report any notable sexual dimorphism in terms of dental status while others prove it. 24,[27][28][29]33,37 This may indicate a regional specificity in this regard.…”
Section: Discussionmentioning
confidence: 97%